Pengaruh terhadap lama perendaman buah rosella (Hibiscus sabdariffa L) melalui uji kadar vitamin C secara spektrofotometri UV-VIS - Shela Binti Bahrum; Anugrah Umar; Jasril Jasril (Politeknik Kesehatan Kemenkes Aceh, 2023)
Background: rosella fruit is a fruit that has a high enough vitamin C content. Vitamin C is needed for collagen production and helps the body's metabolic processes. Vitamin C dissolves easily in water and is easily damaged, so care must be taken to get a high enough content. Vitamin C levels are essential to measure, one of which is by using the UV-VIS spectrophotometry method. This study aims to determine differences in vitamin C levels through the length of soaking rosella fruit, commonly used among the public as an alternative to herbal medicine.Objectives: to determine differences in levels of vitamin C in rosella fruit samples through soaking time as is often done among people who drink rosella fruit boiled water as an alternative to herbal medicine.Methods: the design of this research is experimental research, namely to determine the level of vitamin C in rosella fruit soaking through soaking time (10 minutes, 20 minutes, and 30 minutes). Tests were carried out using UV-VIS Genesis spectrophotometry.Results: the study found that the levels of vitamin C found in rosella fruit soaking for 10 minutes was 117.9 mg/50 g, soaking for 20 minutes was 74.778 mg/50 g, and soaking for 30 minutes was 69.621 mg/50 g.Conclusion: this shows that the level of vitamin C content is higher in 10 minutes of immersion compared to 20 and 30 minutes of immersion. Rosella fruit has the potential as a source of vitamin C, therefore, it is recommended to pay attention to the long soaking time of rosella fruit because the longer the soaking time of rosella fruit, the less vitamin C content in the fruit will be